Peripheral Nerve Regeneration Following Crush Injury to Rat Peroneal Nerve by Aqueous Extract of Medicinal Mushroom Hericium erinaceus (Bull.: Fr) Pers. (Aphyllophoromycetideae) - Wong, Kah Hui; Naidu, Murali; David, Pamela; Abdulla, Mahmood Ameen; Abdullah, Noorlidah; Kuppusamy, Umah Rani; Sabaratnam, Vikineswary (Hindawi, 2011)
Nerve crush injury is a well-established axonotmetic model in experimental regeneration studies to investigate the impact of various pharmacological treatments. Hericium erinaceus is a temperate mushroom but is now being cultivated in tropical Malaysia. In this study, we investigated the activity of aqueous extract of H. erinaceus fresh fruiting bodies in promoting functional recovery following an axonotmetic peroneal nerve injury in adult female Sprague-Dawley rats by daily oral administration. The aim was to investigate the possible use of this mushroom in the treatment of injured nerve. Functional recovery was assessed in behavioral experiment by walking track analysis. Peroneal functional index (PFI) was determined before surgery and after surgery as rats showed signs of recovery. Histological examinations were performed on peroneal nerve by immunofluorescence staining and neuromuscular junction by combined silver-cholinesterase stain. Analysis of PFI indicated that return of hind limb function occurred earlier in rats of aqueous extract or mecobalamin (positive control) group compared to negative control group. Regeneration of axons and reinnervation of motor endplates in extensor digitorum longus muscle in rats of aqueous extract or mecobalamin group developed better than in negative control group. These data suggest that daily oral administration of aqueous extract of H. erinaceus fresh fruiting bodies could promote the regeneration of injured rat peroneal nerve in the early stage of recovery.